The effect of chromium concentration on luminescent properties of alkali-alumina-borate glass-ceramics; Journal of Non-Crystalline Solids; Vol. 521 - Babkina A. I. Alyona Igorevna; Zyrjyanova K. S. Kseniya Sergeevna; Agafonova D. S. Darjya Andreevna; Nuryev R. K. Rustam Kakabaevich; Ignatjev A. I. Andrey Ivanovich; Valiev D. T. Damir Talgatovich (2019, 2019)
Title screen